The Silent Decline of Indonesian Education: A Critical Analysis of the Psychological Dissonance Impact of Adapting Western Education Models - Ardiansyah; Viki Bayu Mahendra; Ashabil Yaqin; Ghufron Ali Sya'ban; Tamim Hasan (Walidem Institute and Publishing, 2026)
Objective: Indonesian education faces a paradox with the adoption of Western educational models like child-centered learning and positive psychology, aimed at enhancing student well-being. However, data reveal declining PISA scores and increasing classroom management issues. This study analyzes the cultural-psychological dissonance caused by the misalignment of these models with Indonesia’s collectivist, hierarchical culture. Theoretical framework: The study integrates Self-Determination Theory (SDT), Baumrind's authoritative discipline model, Bandura’s Social Cognitive Theory, and Hofstede’s cultural dimensions to understand why Western models fail in the Indonesian context, particularly in terms of discipline, motivation, and teacher authority. Literature review: Previous research shows a drop in PISA scores and difficulties in teacher-student interactions due to soft discipline policies. These findings highlight the failure to align Western educational reforms with Indonesian cultural values, leading to confusion, disengagement, and a weakening of teacher authority. Methods: This study uses systematic library research, analyzing empirical studies from 2015 to 2025, employing qualitative content analysis to uncover the underlying psychological and cultural causes of the educational crisis. Results: The shift to permissive education policies has weakened discipline and teacher authority, eroding student motivation. The failure to account for cultural context has exacerbated these issues, with students losing respect for authority figures. Implications: The study advocates for an Authoritative-Restorative model that combines structure with empathy, aligned with Indonesian values, to restore discipline, motivation, and respect in classrooms. Novelty: This paper proposes the Authoritative-Restorative model as a culturally relevant solution to Indonesia’s educational challenges.